Intermittent chemotherapy can retain the therapeutic potential of anti‐CD137 antibody during the late tumor‐bearing state. Issue 1 (9th December 2014) - Tongu, Miki; Harashima, Nanae; Tamada, Koji; Chen, Lieping; Harada, Mamoru
<x xml:space="preserve">Abstract</x> Immunomodulating monoclonal antibodies (mAb) can evoke antitumor T‐cell responses, which are attenuated by regulatory T cells (Treg) and myeloid‐derived suppressor cells (MDSC). Treatment with cyclophosphamide (CP) and gemcitabine (GEM) can mitigate the immunosuppression by Treg and MDSC, respectively. In the current study, we examined the antitumor effects of a combination of local injection with anti‐CD137 mAb and intermittent low‐dose chemotherapy using CP and GEM in subcutaneously established CT26 colon carcinoma. Although a significant antitumor effect was observed when local anti‐CD137 mAb therapy (5 μg) was started early in the tumor‐bearing stage (day 10), no therapeutic efficacy was observed when the mAb therapy was started at a later tumor‐bearing stage (day 17). Analyses of the tumor‐infiltrating immune cells revealed that the number of Gr‐1high/low CD11b+ MDSC started to increase 13 days after tumor inoculation, whereas injection with low‐dose (50 mg/kg) CP and GEM mitigated this increase. In addition, although intermittent injections with low‐dose CP and GEM on days 10 and 18 suppressed tumor growth significantly, additional local injections of anti‐CD137 mAb on days 19, 21, and 23 further augmented the therapeutic efficacy. Cytotoxic T lymphocytes reactive to CT26 and a tumor antigen peptide were induced successfully from the spleen cells of tumor‐cured or tumor‐stable mice. In a bilateral tumor inoculation model, this combination therapy achieved systemic therapeutic effects and suppressed the growth of mAb‐untreated tumors. These results suggest that intermittent immunochemotherapy using CP and GEM could retain the therapeutic potential of anti‐CD137 mAb that is normally impaired during the late tumor‐bearing stage.